Penguatan Ketahanan Keluarga melalui Pemahaman Phubbing sebagai Upaya Penekanan Angka Perceraian di Kabupaten Ponorogo - Maghfiroh, Ana; Yulianti, Dwiana Binti; Dewi, Dian Suluh Kusuma (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
This community service activity aims to provide education and understanding of the phenomenon of phubbing, its impact on the family, and strategies to overcome it. The methods and stages in this program include: 1) the preparation stage, 2) organizing seminars and parenting about phubbing and its impact on the family, and 3) activity reporting. The results of this activity showed an increase in: partners' understanding of the importance of family resilience in maintaining family harmony, understanding of strategies in controlling the use of information media and gadgets in the family, partners' understanding of the phubbing phenomenon, its impact and dangers for family relationships, partners' understanding in maintaining communication in the family and overcoming phubbing.